Literarnost, ponovno - Zupan Sosič, Alojzija (Primerjalna književnost, 2010)
In a literary text, literariness is the central, defining, and essential feature, whereas in a non-literary text it is merely a parallel, marginal, or atypical element. Literariness is namely an intersection of various features and processes established in the relationship between text and context. It is a variable category composed of intratextual and extratextual literariness; the first includes relatively constant features of the literary text such as destructive construction, universality in singularity, polysemy, self-referentiality, and fictionality. In contrast, extratextual literariness is shaped by the following processes: the literary contract, competence, intention, empathy, and literary evaluation.
Keywords: literarna veda; literary science; pripovedna struktura; literarnost